Exposure to violence and associated factors among university students in Ethiopia: A cross-sectional study - Wudinesh Belete Belihu; Tobias Herder; Minilik Demissie Amogne; Jesper Sundewall; Jack Palmieri; Anette Agardh (PLoS ONE, 2025)
Background Violence is a major public health concern with a significant impact on the health and well-being of individuals, families, and communities. Living in a new environment without parental control and experimenting with new lifestyles may increase the risk of violence among university students. Therefore, this study aimed to assess exposure to violence and its associated factors among university students in Ethiopia. Method A cross-sectional study was conducted among 2988 university students from six randomly selected universities in Ethiopia. A two-stage stratified sampling method was used to recruit the study participants. A self-administered questionnaire was utilized to collect information regarding exposure to emotional, physical, and sexual violence. Bivariable and multivariable logistic regression analyses were used to identify factors associated with violence exposure in the last 12 months. Results The prevalence of exposure to any type of violence in the last 12 months was 17.6% (n = 525) (17.9% among males, 16.5% among females). The adjusted odds ratio (AOR) of violence was 2.9 times higher (95% CI 1.6-5.0) among students older than 25 years than those aged 18-20 years. Those students who were in a relationship had 1.4 times higher odds of violence (95% CI 1.0-2.0) than those who were not in a relationship. In addition, those students who were from rural residences before coming to the university had 1.4 times higher odds of violence (95% CI 1.1-1.8) than those from urban residences. The odds of violence among those who consumed alcohol once a week or more in the past month were 2.2 times higher (95% CI 1.3-3.6) than those who did not consume alcohol. Furthermore, the likelihood of violence was 1.6 times higher (95% CI 1.0-2.4) among those who chewed khat and 2 times higher (95% CI 1.3-3.1) among those who used other drugs in the last 12 months. Conclusion Exposure to violence is a challenge for both male and female university students in Ethiopia. Several socio-demographic and behavioral factors were significantly associated with exposure to violence. Therefore, it is crucial for universities and stakeholders to raise awareness about contributing factors to minimize violence, regardless of gender.